Что такое х, если \(3x - sqrt(2(x-3)^2) = 2x + 7-5x\)?

0
0

Что такое х, если \(3x — sqrt(2(x-3)^2) = 2x + 7-5x\)?

0
0

\[x_1=(72+22sqrt2)/(34*2)=(36+11sqrt2)/34\] а также \[x_2=(72-22sqrt2)/(34*2)=(36-11sqrt2)/34\] Объяснение: \[3x-sqrt(2*(x-3)^2)=2x+7-5x\] \[3x-sqrt(2*(x-3)^2)=7-3x\] \[3x+3x-7=sqrt(2*(x-3)^2)\] \[6x-7=sqrt(2*(x-3)^2)\] \[(6x-7)^2=2*(x-3)^2\] \[36x^2-84x+49=2*(x^2-6x+9)\] \[36x^2-84x+49=2x^2-12x+18\] \[34x^2-72x+31=0\] \[Delta=(-72)^2-4*34*31=968=(22sqrt2)^2\] следовательно \[x_1=(72+22sqrt2)/(34*2)=(36+11sqrt2)/34\] а также \[x_2=(72-22sqrt2)/(34*2)=(36-11sqrt2)/34\]

Показан 1 результат